Logicism and Formal Necessity: Reflections on Kant's Modal Metaphysics. Issue 3 (21st August 2018) - Van Cleve, James
Abstract: Logicism is Stang's name for the Leibnizian doctrine that all necessary truths are derivable from identities and definitions. Stang shows that the early Kant opposed this doctrine because he thought the proposition God exists was a counterexample to it; I raise some non-theological counterexamples as well. Formal necessity is the necessity that attaches to a proposition when its truth is grounded in our categories and forms of intuition. Stang treats it as one of several sui generis kinds of necessity in Kant, all of them falling short of logical or metaphysical necessity. I raise several questions for Stang's account, including the following: Can our having the forms we do really explain the necessity of geometry? Is our possession of those forms self-grounding in an objectionable way? How can our forms ground general truths without grounding particular instances of them?